Perception on healthy lifestyle among students in Faculty of Education, UiTM Shah Alam / Noor Aini Hashim - Hashim, Noor Aini (Faculty of Education, 2014)
This study examined the perceptions on healthy lifestyles among students in the Faculty of Education, UiTM Shah Alam. The objective of this study is to evaluate the level of student’s knowledge and understanding about healthy lifestyles. In addition, this study aimed to determine the healthy lifestyle practice among students and to find out the barriers factors that blocking students from engaging in healthy lifestyle. Data were collected from 40 students from the Faculty of Education by using the questionnaire. The results showed that the majority of respondents have a high level of knowledge about a healthy lifestyle, but it was not implemented. Additionally, the study found that healthy lifestyle practice among the respondents is that they are more likely to eat fast food and eating snack or junk food. The main factor or the barriers that blocking respondent to engaging in healthy lifestyle is the poor time management.